Implementasi Media Anak Tangga pada Pelajaran Matematika Kelas III di SD Mundurejo 02 Jember - Mely Agustin Reni Pitasari (Jurnal Pendidikan : Riset dan Konseptual, 2024)
This study aims to determine how the process of implementing mathematics learning using ladder media, especially unit length material, knowing the role given by ladder media in learning mathematics, and knowing the inhibiting and supporting factors of the application of this learning media. This research was conducted on third grade students of Mundurejo 02 Jember Elementary School. The type of research conducted is qualitative by collecting data through observation, interviews, and supporting documentation. The results of the study stated that the learning process of using the stairs media in learning mathematics begins with directions from the teacher and the division of groups. Then proceed each group to do the task by using the stairs media according to the teacher's direction. The role of this staircase media is to attract students in math lessons. The obstacles encountered in the application of this media are related to the duration of time wasted to coordinate students.